AN INTERPRETIVE STUDY OF THE COMMUNICATION NEEDS OF ENGLISH DEPARTMENT STUDENTS AT UNIVERSITY OF MUHAMMADIYAH MALANG - Poedjiastutie, Dwi; Naidi Warnanda, Kharisma; Saputro, Teguh Hadi; Hima, Aninda Nidlomil (Lecturer at the Faculty of Education, University of Muhammadiyah Malang, 2017)
At English Department (ED) UMM, students learn communication for General Purposes (GE) and the generality of the communication materials very much depend on the teachersâ decisions. In other words, teachers can decide any topics and materials depending on the communication books they possessed and read. Even so, many of them by the end of their study period are still not able to speak English fluently. This research is to provide information needed for the curriculum development and classroom instruction through Needs Analysis (NA). The research questions for this study cover (1) what communication skills and competence are expected by ED UMM students? To answer the following questions, an interpretive research paradigm will be employed in the proposed research. In an interpretive research paradigm, theories are constructed from the data rather than theories preceding the data. The data in this research is the participantsâ goals, reasons, motives, feelings, perspectives, and assumptions and these participant perspectives will be viewed through the lens of their cultural contexts. This approach uses three-stage data collection and analysis, namely: FGD (focus-group interview) with ED students. The findings showed: